Leaderless organizations: Identifying leadership vacuum in organizations - Sergey Ivanov; Alex Maritz (Cogent Business & Management, 2023)
Leaders play crucial roles in their enterprises. Most modern organizations today, such as corporations and government departments, have no leaders. About 80% of all organizations have no top structures, and are run by inertia as leaderless organizations. These organizations have pretense-pseudo structures and filled roles, such as CEO, Department Head/Secretary, EVP, VP, and others, but this non-accountable system mostly harms than benefits the organization and its stakeholders. When the eventual crisis unfolds, often because the façade setup has failed to properly prepare the organization for the future, these "leaders" cut resources and lower-level roles out of the organization to continue in the downfall. Sometimes, they even sacrifice their own citizens.
Keywords: 650; Feararchy; General Theory of Managerial Hierarchy; Leaderless Organizations; Leadership Vacuum; Organizational Structure; Requisite Organization Theory